Fabrication of homogeneous nanoparticle/nanoneedle BaTiO3 and Ba0.8Sr0.2TiO3 smooth thin films by simple dip coating - Saini, Mamta; Vivekanand, K.; Poddar, Pankaj; Murty, K. V. G. K.; Thushara, K. S.; Gopinath, Chinnakonda S. (International Journal of Nanotechnology, 2010)
Ferroelectric BaTiO3 (BTO) and Ba0.8Sr0.2TiO3 (BSTO) thin film materials have been successfully prepared by sol-gel processing and simple dip coating on glass and silicon supports. Above thin films were characterised by x-ray diffraction (XRD), Raman spectroscopy, photoelectron spectroscopy, thermal analysis, atomic force microscopy (AFM) and spectroscopic ellipsometry. Phase identification of BaTiO3 and Ba0.8Sr0.2TiO3 was performed by XRD. XRD and Raman spectroscopy investigations demonstrate that thc Ba0.8Sr0.2TiO3 film exhibits tetragonal structure. AFM analysis demonstrates the elongated nanospherical particles on glass substrate and nanowires on silicon substrate, which represent a strong influence of the crystallinity of underlying substrate on the grain morphology in this technique. The thin films on both the substrates are uniformly coated without any pinhole to significant area (similar to 2.5 cm(2)), and this method might be extended to large area uniform coating. Spectroscopic ellipsometric measurements reveal the exact thickness, refractive index and extinction coefficient of the thin films.
Keywords: barium strontium titanate; barium titanate; dip coating; fabrication; ferroelectric material; large area coating; nanotechnology; thin film